AFFIXES IN THE LYRICS OF MICHAEL LEARNS TO ROCK SONGS - Laoli, Citra Indah Maharani (Journal of Language, Literature and Teaching, 2025)
The objective of this study was to identify affixes in the lyrics of Michael Learns to Rock Songs. This study was conducted based on qualitative research method. The data of this study were the lyrics of the five songs from Michael Learns to Rock. The songs were (1) Paint My Love, (2) Sleeping Child, (3) Take Me to Your Heart, (4) That’s Why (You Go Away), and (5) The Actor. The instrument used to collect the data was an observation sheet. Based on the data analysis conducted, it was found that suffixes were the only type of affixes found in the five songs analyzed. From 99 affixes found, there were 99 suffixes (100%). Moreover, there were nine types of suffixes found, namely: suffix -est, -s, -ly, -es, -dom, -ing, -y, -ed, and -ness. Furthermore, suffix –ing (47%) and suffix –s (37%) were the two dominant types of suffixes found in the five songs analyzed. The predominance of –ing (47%) and –s (37%) shows that present participles and plural or third-person singular verb forms are the most frequently used, which aligns with the common linguistic patterns in song lyrics that often emphasize ongoing actions, emotional states, and habitual activities. Overall, the results reinforce previous observations that popular song lyrics typically prioritize simplicity and fluency, relying on basic and frequent English inflectional suffixes to enhance rhythm, rhyme, and listener comprehension. Keywords: affixes, suffixes, lyrics, songs.